Praktik Keamanan Manusia Soka Gakkai International di Indonesia, Filipina, Dan Singapura ketika Pandemi COVID-19 - Muhammad Fikry Anshori; Susy Ong (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2020)
Indonesia, Philippines, and Singapore have the largest number of confirmed COVID-19 cases in Southeast Asia. Soka Gakkai International is a Non-Governmental Organization of Nichiren Buddhists with 2 million members spread across 192 countries, including those three countries. They involved in global issues such as human rights and sustainable development. Then, how are the activities carried out by this organization to support human security in Indonesia, the Philippines, and Singapore during the COVID-19 pandemic? This article attempts to answer this question by using the concept of Non-Governmental Organization and human security. The results show various Soka Gakkai International activities in Indonesia, Philippines, and Singapore from March to July 2020 that support the efforts to protect people from the COVID-19 threat. Also, there is pro and contra among scholars regarding the human security practice of SGI during a pandemic. These can be lessons regarding human security practices amid pandemic.